Low-activated Li-ion mobility and metal to semiconductor transition in CdP2@Li phases1. Issue 12 (28th March 2015) - Eckstein, N.; Krüger, I.; Bachhuber, F.; Weihrich, R.; Barquera-Lozada, J. E.; van Wüllen, L.; Nilges, Tom
<x xml:space="preserve">Abstract</x> Solids with high ion mobility are of broad interest for energy storage applications.